A review of intelligent interactive learning methods - Ukenova, Aru; Bekmanova, Gulmira (Frontiers in Computer Science, 2023)
The development of intelligent interactive learning approaches has received a lot of attention in recent years due to the trend of incorporating intelligent algorithms. Intelligent interactive education tools have a significant positive impact on user engagement, motivation, and social outcomes. This study attempts to explore the existing models, methods and technologies of intelligent interactive learning including virtual and augmented reality. The method of the current study was a semi-systematic literature review. This study is expected to make a substantial contribution to research on the use of intelligent interactive learning applications in e-learning. It supports earlier research and suggests a wide range of pertinent subject areas that might be investigated to progress the field. These findings lead to recommendations for future research on intelligent interactive learning techniques in e-learning.